The forgiveness of debt in Matthew 6 - Nel, Marius (Neotestamentica, 2013)
This article aims to determine if the fifth petition of the Lord's Prayer (Matt 6:12) regards the forgiveness of the monetary debts of others as a precondition for receiving God's forgiveness. It undertakes a brief survey of the socio-economic context of the gospel of Matthew, as well as Matthew's general approach to debt, before analysing the argumentative texture of the Lord's Prayer. It concludes that the fifth petition did not specifically envisage the cancellation of monetary debt as a condition for receiving forgiveness from God.